Ferromagnetic Resonance Investigation in Permalloy Magnetic Antidot Arrays on Alumina Nanoporous Membranes - Aliaga-Vidal, C; Aliaga-Vidal, C; Escrig-Murua, J; Palma-Solorza, J; Michea-Mora, S; Casagrande-Denardin, J (2014)
The magnetic properties of Ni80Fe20 antidot arrays with hole diameters of 18 and 70 nm fabricated by a template-assisted method were investigated using the ferromagnetic resonance technique. Tuning the antidot arrays by changing the hole diameter enables control on the angular dependence of the ferromagnetic resonance field. The scanning electron microscope images reveal a quite regular hexagonal arrangement of the pores, however the angular dependence of the resonance field do not exhibit the six-fold symmetry expected for this symmetry. Micromagnetic simulations performed on a perfect hexagonal lattice, when compared with those made on our real system taken from the scanning microscope images, reveal that the presence of defects in the antidot lattice affects the ferromagnetic resonance field symmetry. © 2013 Elsevier B.V.